Antimicrobial and Cytotoxic Activities of Dillenia pentagyna (Dhaka University Journal of Pharmaceutical Sciences, 2008)
DOI = 10.3329/dujps.v7i1.1228Dhaka Univ. J. Pharm. Sci. 7(1): 103-105, 2008 (June)